Making People Illegal: What Globalization Means for Migration and Law - Dauvergne, Catherine (Cambridge University Press, 2013)
This book explores the relationship between illegal migration and globalization. Under globalizing forces, migration law has been transformed into the last bastion of sovereignty. This explains the worldwide crackdown on extra-legal migration, and informs the shape this crackdown is taking. Even as states ratchet up provisions to end illegal migration, the phenomenon becomes increasingly significant legally, politically, ethically, and numerically. This book makes the innovative argument that the current state of migration law is vital to understanding globalization. It shows the intertwining of refugee law, security, trafficking and smuggling, and new citizenship laws,withparticular attention tohowtheUnited States and theEuropean Union define and defy what counts as global. Making People Illegal evaluates why migration law in the twenty-first century ismarkedly different fromeven the recent past, and argues that this is a harbinger of paradigm shift in the rule of law.